Pharmacokinetics of Pantoprazole and Pantoprazole Sulfone in Goats After Intravenous Administration: A Preliminary Report - Smith, Joe S.; Mochel, Jonathan P.; Soto-Gonzalez, Windy M.; Rahn, Rebecca R.; Fayne, Bryanna N.; Escher, Olivia G.; Geletka, Anastasia M.; Harvill, Lainey E.; Bergman, Joan B.; Cox, Sherry (Frontiers in Veterinary Science, 2021)
Background: Ruminant species are at risk of developing abomasal ulceration, but there is a lack of pharmacokinetic data for anti-ulcer therapies, such as the proton pump inhibitor, in goats. Objective: The primary study objective was to estimate the plasma pharmacokinetic parameters for pantoprazole in adult goats after intravenous administration. A secondary objective was to describe the pharmacokinetic parameters for the metabolite, pantoprazole sulfone, in goats. Methods: Pantoprazole was administered intravenously to six adult goats at a dose of 1 mg/kg. Plasma samples were collected over 36 hours and analyzed via reverse phase high performance liquid chromatography for determination of pantoprazole and pantoprazole sulfone concentrations. Pharmacokinetic parameters were determined by non-compartmental analysis. Results: Plasma clearance, elimination half-life, and volume of distribution of pantoprazole were estimated at 0.345 mL/kg/min, 0.7 h, and 0.9 L/kg, respectively following IV administration. The maximum concentration, elimination half-life and area under the curve of pantoprazole sulfone were estimated at 0.1 μg/mL, 0.8 h, and 0.2 hr*μg/mL respectively. The global extraction ratio was estimated 0.00795 ± 0.00138. All animals had normal physical examinations after conclusion of the study. Conclusion: The reported plasma clearance for pantoprazole is lower than reported for foals, calves, and alpacas. The elimination half-life appears to be less than that reported for foals and calves. Future pharmacodynamic studies are necessary for determination of the efficacy of pantoprazole on acid suppression in goats.